EKSPLORASI POTENSI FAUNA DI KAWASAN SUNGAI CIPUNAGARA KABUPATEN SUBANG SEBAGAI REKOMENDASI PENGEMBANGAN KAWASAN KONSERVASI - Agus Yani (Fakultas Kehutanan Universitas Winaya Mukti, 2022)
The variety of fauna is one of the certain natural wealth of Indonesia. Yet human characterisic to destroy forest has inflicted a loss. Therefore the fauna in its real habitat needs more attention so it may become a media in conserving the fauna and the habitat in order to save it for the future generation. The object of research is help to preserve the existing fauna and conservation area. The method of research by transect path and interviewing people around Wildlife Reserve of Cipunagar River, the observation on the location was done by following direction and position of transect diameter slowly and at the same time making note of any fauna species found. The result of the research that was done in wildlife resrve of Cipunagara River showed that there were 12 species of 8 families, are Panthera tigris sondaicus, Panthera pardus melas, Nisaetus bartelsi, Pteropus vampyrus, Trachypithecus auratus, Presbytis comate, Hystrix javanica, Sus verrucosus, Macaca fascicularis, Gallus gallus, and Colluricincla sp. The recommendation of fauna potential and conservation area is Taman Hutan Raya.